Індукована хіміотерапією аменорея у хворих на рак молочної залози: основні механізми та діагностичні критерії порушення функції яєчників - Щепотін, І. Б.; Зотов, О. С.; Анікусько, М. Ф.; Любота, І. І.; Любота, Р. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
Occurrence of amenorrhea during chemotherapy in patients with breast cancer, some authors regard as a method of drug suppression of ovarian function. Chemotherapy-induced amenorrhea, due to the toxic effect of chemotherapy on the ovaries. Its appearance depends on the age of the patient, and the duration of chemotherapy protocol, as well as the cumulative dose of chemotherapy. Chemotherapy-induced amenorrhea occurs in 70% of premenopausal women, 40% of patients with breast cancer before age 40 years and 90% of women over 40. Several clinical trials show that the occurrence of amenorrhea during chemotherapy in patients with hormone-dependent breast cancer before age 50 improves survival. However, the absence of menstruation due to chemotherapy is not always an indication of adequate suppression of hormone-producing function of the ovaries and / or the onset of menopause. In this revue the main physiological mechanisms of chemotherapy-induced amenorrhea, as well as criteria for the diagnosis and clinical significance of various disorders of ovarian-menstrual cycle in premenopausal patients with breast cancer are discussed.